Pengaruh Social Media Marketing, Gamification, dan E-WoM Terhadap Customer Engagement Pada KFC di Kota Surabaya - Chelsea Jeffriani Gunawan; Valencia Vanessa Timisela; J.E Sutanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to examine the influence of social media marketing, gamification, and E-WoM on customer engagement. The population in this study is KFC customers in Surabaya. The sampling technique used is purposive sampling, with a total sample of 194 respondents. Data were analysed using the SPSS version 26 program. The results indicate that all the studied factors significantly influence customer engagement. In addition, this study supports the achievement of SDG 9 (Industry, Innovation, and Infrastructure) by demonstrating how the adoption of digital marketing strategies and technology based innovations, such as social media marketing, gamification, and E-WoM, can enhance industrial competitiveness and strengthen sustainable business performance within the food and beverage sector, especially fast food.